2011
DOI: 10.1016/j.eurpsy.2010.03.012
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of childhood ADHD history in women with fibromyalgia

Abstract: Fibromyalgia and ADHD share some clinical features, and a reduced dopamine function has been proposed for both disorders. Here we found, in a large sample of fibromyalgia female patients, a higher frequency of childhood ADHD antecedent when compared with healthy women. Our data suggest that Fibromyalgia and ADHD have some common etiopathological mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 9 publications
4
18
0
2
Order By: Relevance
“…Therefore, we set out here, in an exploratory fashion, to examine the potential for EEG-BF in improving FMS features, as measured by changes in a CPT and certain clinical findings. A CPT seemed appropriate in measuring a portion of the CNS lesion in FMS since it is an objective and easily reproducible test directly affected by CNS function, particularly in ADHD (Epstein et al 2003), a disorder that occurs with striking frequency in FMS (Reyero et al 2010). CPT results might also be helpful to investigators interested in psychometric testing in FMS since CPT scores may correlate with the affective state (Chen et al 2004;Bedwell et al 2009), even in the pre-clinical setting (Bove 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, we set out here, in an exploratory fashion, to examine the potential for EEG-BF in improving FMS features, as measured by changes in a CPT and certain clinical findings. A CPT seemed appropriate in measuring a portion of the CNS lesion in FMS since it is an objective and easily reproducible test directly affected by CNS function, particularly in ADHD (Epstein et al 2003), a disorder that occurs with striking frequency in FMS (Reyero et al 2010). CPT results might also be helpful to investigators interested in psychometric testing in FMS since CPT scores may correlate with the affective state (Chen et al 2004;Bedwell et al 2009), even in the pre-clinical setting (Bove 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Dans des hypothèses impliquant le dysfonctionnement dopaminergique chez les patients FM, une plus grande fréquence d'antécédents de trouble déficitaire de l'attention avec hyperactivité (TADHA) a été montrée en comparant plus de 200 patientes FM à environ 200 sujets contrôles [40]. On trouve aussi des troubles du sommeil montrant une diminution du temps passé en sommeil paradoxal et sommeil long profond, ainsi que de nombreux réveils nocturnes qui pourraient donc être associés à l'asthénie ressentie chez ces patients [41].…”
Section: Autres Troubles Psychiatriques Associésunclassified
“…However, there are only a few previous reports on rates of patients with FM [8] [9] or CFS [13] who are also diagnosed with ADHD. Similarly, the limited studies performed to date have reported varied results with regard to the effects of central nervous stimulant treatments for ADHD on pain symptoms [5] [6] [7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ADHD should be included as a potential differential diagnosis during assessment for these disorders if patients complain of widespread muscle pain, tiredness, and sleep problems without significant physical abnormalities. A high rate of concurrent ADHD (25% -80%) has been reported in individuals with FM [7] [8], and it has also been reported that 32.3% of patients with FM suffered from ADHD during early childhood, compared with 2.5% in a control group [9]. Moreover, patients with FM exhibit significant memory problems more often than healthy controls, and this is reportedly due to heightened distractibility among patients with FM [10].…”
Section: Introductionmentioning
confidence: 99%